Sporadic renal hemangioblastoma with CA9, PAX2 and PAX8 expression: diagnostic pitfall in the differential diagnosis from clear cell renal cell carcinoma - Kuroda, Naoto; Agatsuma, Yoshiko; Tamura, Masato; Martinek, Petr; Hes, Ondrej; Michal, Michal (International journal of clinical and experimental pathology, 2015)
To date, 13 cases of sporadic renal hemangioblastoma have been reported. In this article, we report such a case that might cause the diagnostic pitfall. A 37-year-old Japanese was found to have a renal mass by periodic medical check-up. He underwent radical nephrectomy. Macroscopically, the tumor was well-defined without fibrous capsule and the cut surface of the tumor exhibited light brown to gray-tan color without hemorrhage or necrosis. Microscopically, the tumor was made up of large polygonal to short spindle cells with eosinophilic cytoplasm with occasional vacuolization and abundant arborizing capillary network. Immunohistochemically, neoplastic cells showed diffuse positivity for inhibin-alpha, S-100 protein, vimentin, CA9, PAX2 and PAX8, but negativity for cytokeratin CAM5.2, alpha smooth muscle actin, Melanosome, Melan A, TFE3 and cathepsin K. In genetic analyses, this tumor showed no changes of VHL gene mutation, hypermethylation and loss of heterozygosity of chromosome 3p. Additionally, G-band karyotype and array comparative genomic hybridization studies showed a normal chromosome. In conclusion, the positivity for CA9, PAX2 and PAX8 in sporadic renal hemangioblastoma may cause the critical diagnostic pitfall in the differential diagnosis from clear cell renal cell carcinoma. Pathologists need to pay attention to systemic evaluation including macroscopic, microscopic and immunohistochemical findings. In some cases, molecular genetic study may be necessary.
Keywords: PAX8; nádory ledvin; transkripční faktor PAX8; PAX2; Male; karcinom z renálních buněk; antigeny nádorové; Adult; Kidney Neoplasms; Diagnosis, Differential; dospělí; mužské pohlaví; kidney; Paired Box Transcription Factors; PAX2 Transcription Factor; transkripční faktor PAX2; hemangioblastom; karboanhydrasa IX; transkripční faktory paired box; lidé; Biomarkers, Tumor; Humans; diferenciální diagnóza; Antigens, Neoplasm; Carbonic Anhydrases; Carcinoma, Renal Cell; Hemangioblastoma; CA9; PAX8 Transcription Factor; Carbonic Anhydrase IX; karboanhydrasy; nádorové biomarkery